Human rights in India - Juss, Satvinder S. (Routledge research in human rights law, 2020)
"This volume presents an integrated collection of essays around the theme of India's failure to grapple with the big questions of human rights protections affecting marginalized minority groups in the country's recent rush to modernization. The book traverses a broad range of rights violations from: gender equality to sexual orientation, from judicial review of national security law to national security concerns, from water rights to forest rights of those in need, and from the persecution of Muslims in Gulberg to India's parallel legal system of Lok Adalats to resolve disputes. It calls into question India's claim to be a contemporary liberal democracy. The thesis is given added strength by the authors' diverse perspectives which ultimately create a synergy that stimulates the thinking of the entire field of human rights, but in the context of a non-western country, thereby prompting many specialists in human rights to think in new ways about their research and the direction of the field, both in India and beyond"--